La asociación estadística entre inflación e independencia del Banco Central The statistical relationship between inflation and independence of the Central Bank - Cargill Thomas (Cuadernos de Economía, 1996)
Este artículo revisa la evidencia empírica sobre la asociación estadística entre medidas formales de independencia del Banco Central y la inflación. Demuestra que el desempeño inflacionarios del Banco del Japón y de la Reserva Federal contradice la existencia de esa asociación y concluye que en las discusiones sobre la reestruturación de los bancos centrales para estabilizar los precios no debería dar tanta importancia a dicha asociación estadística, pues los resultados no son estadísticamente robustos. This article reviews the empirical evidence about the statistical relation ship between formal measures of central bank independence and inflation. It demonstrates that the inflationary performance of the Bank of Japan and the Federal Reserve contradict: the existence of that relationship, and concludes that in discussions about the restructuring of central banks to stabilize prices there should not be so much importance attached to that statistical relationship, as the resultsare not statistically robusto.